Aktivitas antimikroba, karakteristik fisikokimia, dan hedonik gel biosanitizer ekstrak daun kelor (Moringa oleifera) [Antimicrobial activity, physicochemical and sensory characteristic of Moringa oleifera leaf extract biosanitizer gel] - Titi Rohmayanti; Rosy Hutami; Maryam Jamila (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Moringa leaves have bioactive compounds of flavonoids and tannins, which can be used as antimicrobials to substitute triclosan and glycerol compounds in commercial sanitizer gels. This study aims to determine the antimicrobial activity, physicochemical characteristics, and sensory properties of the moringa leaf extract of the bio-sanitizer gel. The research consisted of two stages: the extraction of Moringa leaves and the stages of making bio-sanitizer gel. The study used a factorial completely randomized design (CRD) with two factors: the type of solvent and the ratio of sample to solvent. Data were analyzed using variance (ANOVA) and Duncan's Range Test (DMRT). The results showed that all samples added to Moringa leaf extract had an antibacterial activity with inhibition zone values that did not differ between treatments within a range of 2.5-3.0 mm. All samples of Moringa leaf extract bio-sanitizer gel have the potential to inhibit E.coli and S.aureus bacteria. The treatment selected for this study was a bio-sanitizer gel of Moringa leaf extract with ethanol solvent and concentration of 1:6 with a pH value (3.90), viscosity (5.57), homogeneous, and having the preferred sensory value (aromatic = 6.47, color = 5.89, viscosity = 5.54, tackiness = 5.48, overall = 5.95).